Development and Validation of Electronic Quality Measures to Assess Care for Patients With Transient Ischemic Attack and Minor Ischemic Stroke. Issue 9 (September 2017) - Bravata, Dawn M.; Myers, Laura J.; Cheng, Eric; Reeves, Mathew; Baye, Fitsum; Yu, Zhangsheng; Damush, Teresa; Miech, Edward J.; Sico, Jason; Phipps, Michael; Zillich, Alan; Johanning, Jason; et al.
Abstract : Background—: Despite interest in using electronic health record (EHR) data to assess quality of care, the accuracy of such data is largely unknown. We sought to develop and validate transient ischemic attack and minor ischemic stroke electronic quality measures (eQMs) using EHR data. Methods and Results—: A random sample of patients with transient ischemic attack or minor ischemic stroke, cared for in Veterans Health Administration facilities (fiscal year 2011), was identified. We constructed 31 eQMs based on existing quality measures. Chart review was the criterion standard for validating the eQMs. To evaluate eQMs in terms of eligibility, we calculated the proportion of patients who were genuinely not eligible to receive a process (based on chart review) and who were correctly identified as not eligible by the EHR data (specificity). To assess eQMs about classification of whether patients received a process, we calculated the proportion of patients who actually received the process (based on chart review) and who were classified correctly by the EHR data as passing (sensitivity). Seven hundred sixty-three patients were included. About eligibility, specificity varied from 25% (brain imaging; carotid imaging) to 99% (anticoagulation quality). About pass rates, sensitivity varied from 30% (antihypertensive class) to 100% (coronary risk assessment; international normalized ratio measured). The 16 eQMs with ≥70% specificity in eligibility and ≥70% sensitivity in pass rates included coronary risk assessment, international normalized ratio measured, HbA1c measurement, speech language pathology consultation, anticoagulation for atrial fibrillation, discharge on statin, lipid management, neurology consultation, Holter, deep vein thrombosis prophylaxis, oral hypoglycemic intensification, cholesterol medication intensification, antihypertensive intensification, antihypertensive class, carotid stenosis intervention, and substance abuse referral for alcohol. Conclusions—: It is feasible to construct valid eQMs for processes of transient ischemic attack and minor ischemic stroke care. Healthcare systems with EHRs should consider using electronic data to evaluate care for their patients with transient ischemic attack and to complement and expand quality measurement programs currently focused on patients with stroke. Abstract : Supplemental Digital Content is available in the text.